Single atom catalysis: a decade of stunning progress and the promise for a bright future - Sharon Mitchell (Nature Portfolio, 2020)
Controlling the hybridization of single atoms in suitable host materials opens unique opportunities for catalyst design, but equally faces many challenges. Here, we highlight emerging directions from the last, highly productive, decade in single-atom catalysis and identify frontiers for future research.